2018
DOI: 10.3847/2041-8213/aadb3d
|View full text |Cite
|
Sign up to set email alerts
|

Inversion Angle of Phase-polarization Curve of Near-Earth Asteroid (3200) Phaethon

Abstract: The linear polarization degree (referred to the scattering plane, P r ) as a function of the solar phase angle, α, of solar system objects is a good diagnostic to understand the scattering properties of their surface materials. We report P r of Phaethon over a wide range of α from 19 • .1 to 114 • .3 in order to better understanding properties of its surface materials. The derived phase-polarization curve shows that the maximum of P r , P max , is >42.4% at α >114 • .3, a value significantly larger than those … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…2011) measured ground and sieved samples whose maximum particle sizes were controlled by their device, while minimum sizes were not, and found that P max depends on the maximum particle size but does not exceed 29 per cent (for Allende, CV3 chondrite with the particle size < 500 μm ). Shinnaka et al 2018 ). This fact suggests that the albedos of these asteroids and carbonaceous chondrites are similar to one another.…”
Section: Albedo-p Max Relationmentioning
confidence: 77%
See 3 more Smart Citations
“…2011) measured ground and sieved samples whose maximum particle sizes were controlled by their device, while minimum sizes were not, and found that P max depends on the maximum particle size but does not exceed 29 per cent (for Allende, CV3 chondrite with the particle size < 500 μm ). Shinnaka et al 2018 ). This fact suggests that the albedos of these asteroids and carbonaceous chondrites are similar to one another.…”
Section: Albedo-p Max Relationmentioning
confidence: 77%
“…5 ), where h denotes the polarimetric slope parameter (see equation ( 2). In the plot, we included two B-type asteroids, Phaethon (Shinnaka et al 2018 ) and Bennu (Cellino et al 2018 ), for comparison, although Phaethon's P min value has not been determined to date. As we mentioned in Section 3.1, h is a good proxy for geometric albedo, showing that samples with high albedos are distributed leftward, while those with lower albedos are distributed rightward.…”
Section: H -P Min Relationmentioning
confidence: 99%
See 2 more Smart Citations
“…Even at r H = 1 AU, particles smaller than 5 µm can be expelled. Selective loss of small particles from Phaethon is suggested by polarization studies and could result from this cause (Ito et al 2018), although the interpretation is not unique (Shinnaka et al 2018).…”
Section: Point Sourcesmentioning
confidence: 99%